2021
DOI: 10.3390/fermentation7030177
|View full text |Cite
|
Sign up to set email alerts
|

Survivability of Collagen-Peptide Microencapsulated Lactic Acid Bacteria during Storage and Simulated Gastrointestinal Conditions

Abstract: The intracellular homeostasis of lyophilized lactic acid bacteria (LAB) is destroyed by extreme cold stress, resulting in decreased stability. This study aimed to verify the validity of collagen as a potential protective agent for improving microbial stability deteriorated by freezing. The collagen types used in this study were low molecular weight collagen (LC) of less than 1000 Da and low molecular weight collagen-peptide (LCP) of less than 300 Da. By the accelerated stability test according to the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Yerlikaya et al [ 64 ] showed the highest viability for L. acidophilus strains and the lowest for L. casei during 30 days of storage. Kim et al [ 69 ] showed that collagen has a protective effect and increases the viability of probiotic strains and enhances bacterial stability, survival in the gastrointestinal tract, and heat resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Yerlikaya et al [ 64 ] showed the highest viability for L. acidophilus strains and the lowest for L. casei during 30 days of storage. Kim et al [ 69 ] showed that collagen has a protective effect and increases the viability of probiotic strains and enhances bacterial stability, survival in the gastrointestinal tract, and heat resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The interindividual variability in recovering the BT01 cells may be associated with the subjects' differences in genetics, as well as dietary patterns, which could affect gastric conditions, and thus the survival of a probiotic strain. [40][41][42] Furthermore, the effect of different cryoprotectants on probiotic strain survival has always been explained on the basis of in vitro conditions mimicking the gastric environment, [12,19,43] and up to date, there is no clear in vivo evidence demonstrating differences in probiotic survival through human GIT lyophilized with different cryoprotectants.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Various cryoprotectants have been explored to examine their in vitro ability to protect probiotic cells from stress factors such as low pH, simulated gastric juice, or bile salts. [10][11][12][13] However, not enough is known how those cryoprotectants influence the faith of probiotics in human GIT after ingestion. One way of evaluating the ability of probiotic strains to survive human GIT are interventional recovery studies that rely on probiotic quantification in human feces after administration.…”
Section: Introductionmentioning
confidence: 99%
“…lactis MG741, and Streptococcus thermophilus MG5140) to investigate the efficacy of a novel additive in bacterial protection nunder different conditions. Kim et al [4] determined that low-molecular-weight collagen-peptide is a stability enhancer for various probiotics and can improve viability after freeze-drying, simulated gastrointestinal conditions, and heat treatment.…”
mentioning
confidence: 99%